Temporal transcriptomics uncover dynamic interactions between pathogenic Escherichia coli and phage vB_Eco_K1B4 - Wang, Guoliang; Liu, Xin; Qin, Junjun; Wang, Yunhan; Ji, Bingzhen; Sun, Jing; Wang, Yanqiang; Zhang, Lin; Zhang, Lili; Lulong, Chunhui; Cai, Miao; Zhang, Yunxia; et al. (Frontiers in Microbiology, 2025)
Pathogenic Escherichia coli has a serious impact on animal husbandry. Currently, people mainly prevent pathogenic bacteria by injecting antibiotics into livestock. However, such frequent use of antibiotics accelerates the development of bacterial resistance and affects people’s health. Using bacteriophages to hunt down pathogenic bacteria has become an efficient method. In this study, we identified and characterized the K1 capsular vB_Eco_K1B4 bacteriophage and used RNA-seq analysis to profile the phage transcripts during the E. coli infection phase. The experimental results showed that bacteriophage vB_Eco_K1B4 still had a survival rate of over 50% in a 70 °C water bath for 1 h, and could survive for a short period at low temperatures. Not only that, vB_Eco_K1B4 also has a high tolerance for relatively extreme pH environments, so this bacteriophage has the potential to inhibit pathogenic bacteria. This study further explores the transcriptional regulation mechanism during the interaction between bacteriophages and hosts. Differentially expressed genes analysis, GO enrichment, and other analysis results show that vB_Eco_K1B4 can accurately regulate the host’s transcriptional resources, while inhibiting the expression of genes related to host structural component formation and upregulating the expression of genes related to host energy metabolism. Moreover, vB_Eco_K1B4 also impacts the host’s defense mechanism against bacteriophages. These transcriptome data provide a more thorough understanding of the cellular response of E. coli to phage infection and aid in understanding the phage-host interaction at the transcriptomic level.